TERRORISM: GLOBAL THREATS AND HUMAN SECURITY - Husni Thamrin (Awang Long Law Review, 2018)
Terrorism is an act that can threaten globally and human security. There are seven components of human security according to UNDP (2004) whose fulfillment must be the responsibility of the government of each country. The seven components can be simplified into two main components, namely freedom from fear and freedom from want (free from inability to own). This research is a normative legal research, using a legislative and conceptual approach, then analyzed qualitatively and presented descriptively. The results show that first, terrorism can be a global threat and human security. There are at least 106 countries around the world that have experienced at least one terrorism attack. This figure is up 11 points from the previous year, where only 95 countries have ever been the destination of terrorism attacks. Second, a conceptual framework such as “Global Antiterrorism Governance” is needed to be agreed upon by all countries in the world, which can be used as a basis for combating global terrorism.